2015
DOI: 10.1128/jb.00446-15
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of DNA Replication Initiation by Chromosome Structure

Abstract: Recent advancements in fluorescence imaging have shown that the bacterial nucleoid is surprisingly dynamic in terms of both behavior (movement and organization) and structure (density and supercoiling). Links between chromosome structure and replication initiation have been made in a number of species, and it is universally accepted that favorable chromosome structure is required for initiation in all cells. However, almost nothing is known about whether cells use changes in chromosome structure as a regulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 101 publications
2
25
0
1
Order By: Relevance
“…Similarly, its been shown that high transcriptional activity also gives rise to net negative chromosomal supercoiling, especially near the origin of replication where several highly-expressed rRNA genes reside. This supercoiling should facilitate DNA melting, again leading to earlier replication times [41]. In light of these considerations, we anticipated lower ρ ( k t , t r ) values than were in fact observed among our best-performing matrices.…”
Section: Finding Extrinsic Noise Correlations That Fit Experimentmentioning
confidence: 83%
“…Similarly, its been shown that high transcriptional activity also gives rise to net negative chromosomal supercoiling, especially near the origin of replication where several highly-expressed rRNA genes reside. This supercoiling should facilitate DNA melting, again leading to earlier replication times [41]. In light of these considerations, we anticipated lower ρ ( k t , t r ) values than were in fact observed among our best-performing matrices.…”
Section: Finding Extrinsic Noise Correlations That Fit Experimentmentioning
confidence: 83%
“…En effet, en se liant à des séquences opératrices (les boîtes DnaA) qui sont présentes aux abords de l'origine de réplication, DnaA, liée à l'ATP, stimule l'ouverture de la double hélice d'ADN et facilite l'accès à la machinerie de réplication d'ADN appelée réplisome [2]. Réguler la quantité totale de DnaA, ou la proportion de DnaA liée à l'ATP, constitue donc un moyen efficace pour les bactéries de contrô-ler précisément l'initiation de la réplication d'ADN.…”
Section: Contrôle Métabolique De La Réplication D'adn Initiation De Lunclassified
“…As discussed above, DnaA and λ O utilize the protein-induced ΔLk to open/melt the AT-rich DUE of replication origins to initiate DNA replication Grimwade 2009, 2015;Magnan and Bates 2015;Rajewska et al 2012;Wolanski et al 2014). Additionally, the nucleoprotein complexes by these replication initiators functioning as a DNA topological barrier (Leng et al 2004(Leng et al , 2011Leng and McMacken 2002) block, confine, and capture transcription-coupled DNA supercoiling, which helps open/melt DUE of replication origins and facilitates DNA replication initiation (Chung 1996).…”
Section: Conclusion and Biological Effectsmentioning
confidence: 99%
“…Nevertheless, DnaAmediated DNA wrapping (winding or unwinding/ΔLk) is critical for the opening of DUE (Duderstadt et al 2011). Other factors such as (−) supercoiling and HU may also help melt/open DUE of OriC (Hwang and Kornberg 1992;Magnan and Bates 2015).…”
Section: Bacterial Dna Replication Initiators: λ O and Dnaamentioning
confidence: 99%